Induction Of Direct Somatic Embriogenesis Of Chrysanthemum In Ms And Naa Media Combined With Some Cytokinin Concentrations - Hestia Sualang; Edy F. Lengkong; Pemmy Tumewu (Sam Ratulangi University, 2023)
This study aims to determine the effect of using MS media and ZPT NAA combined with several concentrations of cytokinins, namely BAP and Kinetin on somatic embryogenesis as seen from the growth of shoots of chrysanthemum (Chrysanthemum sp.). This research was conducted from June 2022 to October 2022 at the Genetics Laboratory of the Faculty of Agriculture, University of Sam Ratulangi. This study used a completely randomized design (CRD) with 7 treatments namely A (NAA 2.0 ppm); AB1 (NAA 2.0 ppm + BAP 1.0 ppm); AB2 (NAA 2.0 ppm + BAP 2.0 ppm); AB3 (NAA 2.0 ppm + BAP 3.0 ppm); AK1 (NAA 2.0 ppm + Kinetin 1.0 ppm); AK2 (NAA 2.0 ppm + Kinetin 2.0 ppm); AK3 (NAA 2.0 ppm + Kinetin 3.0 ppm). Each treatment was repeated 7 times resulting in 49 experimental units. Observational data were analyzed using the ANOVA test and continued with the 5% LSD test. The results showed that MS medium and growth regulator NAA combined with cytokinins could induce somatic embryogenesis of chrysanthemum plants, where concentrations of NAA 2.0 ppm and BAP 2.0 ppm had the best effect on the number and height of explant shoots. The concentration of NAA growth regulator at 2.0 ppm gave the highest number of roots and when combined with cytokinins it reduced the number of roots. Keywords: Growth Regulatory Substances, Somatic Embryogenesis, Chrysanthemum. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media MS dan ZPT NAA yang dikombinasikan dengan beberapa konsentrasi sitokinin yaitu BAP dan Kinetin terhadap embriogenesis somatik yang dilihat dari pertumbuhan tunas tanaman krisan (Chrysanthemum sp.). Penelitian ini dilaksanakan pada bulan Juni 2022 sampai Oktober 2022 di Laboratorium Genetika Fakultas Pertanian Universitas Sam Ratulangi. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 7 perlakuan yaitu A (NAA 2,0 ppm); AB1 (NAA 2,0 ppm + BAP 1,0 ppm); AB2 (NAA 2,0 ppm + BAP 2,0 ppm); AB3 (NAA 2,0 ppm + BAP 3,0 ppm); AK1 (NAA 2,0 ppm + Kinetin 1,0 ppm); AK2 (NAA 2,0 ppm + Kinetin 2,0 ppm); AK3 (NAA 2,0 ppm + Kinetin 3,0 ppm). Masing-masing perlakuan yang diulang 7 kali menghasilkan 49 satuan percobaan. Data hasil pengamatan dianalisis dengan menggunakan uji ANOVA dan dilanjutkan dengan uji BNT 5%. Hasil penelitian menunjukkan bahwa media MS dan zat pengatur tumbuh NAA yang dikombinasikan dengan sitokinin dapat menginduksi embriogenesis somatik tanaman krisan, dimana konsentrasi NAA 2,0 ppm dan BAP 2,0 ppm memberikan pengaruh terbaik terhadap jumlah dan tinggi tunas ekplan. Konsentrasi zat pengatur tumbuh NAA 2,0 ppm memberikan jumlah akar terbanyak dan apabila dikombinasikan dengan sitokinin dapat menekan jumlah akar. Kata kunci : Zat Pengatur Tumbuh, Embriogenesis Somatik, Krisan